ANALYSIS OF GENERATION Z CONSUMER BEHAVIOR IN THE DIGITAL ERA - Dyah Ika Kirana Jalantina; Maria Magdalena Minarsih (Jurnal Bingkai Ekonomi (JBE), 2025)
The rapid development of technology today has changed consumer behavior in shopping for products or services. The large number of computer applications that replace human services, such as many market places, online motorcycle taxis, online loans and even opening savings accounts online, makes consumers rely on these applications to support their daily needs, including supporting their work. Consumer knowledge of a product or service increases along with the many types of information received. This research is a qualitative descriptive study, with data collection directly from Gen Z consumers (aged 12 years to 27 years). This research aims to determine changes in consumer behavior amid the rise of online shopping applications and systems. The research results show that Gen Z consumer behavior has changed to digital consumer behavior so that online sales are more attractive to consumers.